Pengaruh CAR, FDR, dan BOPO Terhadap ROA pada Studi kasus BCA Syariah periode (Tahun 2018 – 2022) - Reines Vinia; Agung Wahyudi (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The purpose of this research is to determine the extent to which the capital adequacy ratio (CAR), Financing to Deposit Ratio (FDR), and the operational expense ratio (BOPO) have an effect on the profitability of BCA Syariah. The return on invested capital (ROA) is the metric that is used to analyse these elements. In terms of methodology, the research is quantitative. This information is included in the yearly report for 2018-2022 that is provided by BCA Syariah. A thorough selection was made for the sample. A multiple linear regression analysis was used in this investigation, and the statistical software tool IBM SPSS version 23 was utilised for the analysis. According to the findings of the multiple linear regression analysis, the independent variables CAR, FDR, and BOPO were able to explain the dependent variable ROA concurrently. This was the case all three variables individually. The correlation between the variable FDR and ROA is positive, although it is not statistically significant. When it comes to ROA, both the CAR factor and the BOPO factor have a counterproductive effect.